Marriage with the Transfer of a Nasab Guardian to Teungku Dayah According to Islamic Law (Case Study in Ingin Jaya District, Aceh Besar Regency): Pernikahan Dengan Peralihan Wali Nasab Kepada Teungku Dayah Menurut Hukum Islam (Studi Kasus Di Kecamatan Ingin Jaya Kabupaten Aceh Besar) - Maghfirah, Maghfirah (El-Hadhanah : Indonesian Journal Of Family Law And Islamic Law, 2023)
This research was motivated by a case in the Ingin Jaya District, Aceh Besar Regency, where there was a marriage with the transfer of the nasab guardian to Teungku Dayah in accordance with Islamic law. A wakalah or transition contract is essentially a contract used by someone if the guardian of the nasab marriage needs someone else to do something that he cannot do himself and asks someone else to do it with the consent of both parties. Therefore, the researcher is interested in researching what factors led to the transfer of marriage guardianship from the nasab guardian to Teungku Dayah and what Islamic Law provisions mean for the process of transferring the nasab marriage guardian to Teungku Dayah. The research methods used are field research and library research. The results of the research state that provisions in Islamic law allow transition or representation to Teungku Dayah due to various factors including ungodly abandoning Allah SWT commands such as abandoning obligatory prayers, carrying out Allah SWT prohibitions such as disobedience, gambling, nervousness or embarrassment in public, old age such as being senile, his eyes are blurry, and his body is shaking. Furthermore, the view of Islamic law regarding the process of transferring the guardian of the nasab marriage to Teungku Dayah is a process that must be gone through, namely that the guardian of the nasab and the person who replaces the position of guardian of the nasab must carry out a wakalah contract before the marriage takes place. The legal transition was carried out because it was seen as a form of mutual help based on goodness and piety commanded by Allah SWT and His messenger.